DESIGN OF PLC BASED TEMPERATURE CONTROL SYSTEM FOR FOOD STABILITY TEST CHAMBER - Jan Setiawan; Abdurahman Abdurahman; Sunardi Sunardi; Sugeng Sugeng; Angga Muhamad Syukur (Sebatik, 2022)
A stability test chamber simulates specific environmental conditions and tests a product or material in the manufacturing stage. The tested product or material is then analyzed about its shelf-life estimation related to the state and durability of the product for a certain period. The main parameter that must control accurately is temperature. Programmable Logic Controller (PLC) as an industrial computer control system has been widely used. In this paper, the temperature control system was designed based on PLC and supervisory control and data acquisition (SCADA). The PLC and SCADA would indirectly control the heater. The PLC was feeded from the temperature sensor for real-time temperature inside the test chamber. Received temperature value, compared to the temperature set point. The validation and verification of controlled temperature inside the chamber were also investigated. The system was designed on a miniaturized chamber using commercial PLC and SCADA, Stepper motor, slide regulator, heater, and the temperature sensor PT100. The temperature test point for validation and verification was performed at 35 °C, 45 °C, and 55 °C. The result showed that The PT100 successfully had an excellent response to the temperature test point. The correction value for temperature is as high as 0.6 °C with a deviation of 1 %.